S79 Sputum Inflammatory Cell Profile in Children with Acute Asthma and Following Recovery. (19th November 2012) - Staley, KG; Fisher, G; Brightling, CE; Bradding, P; Parker, D; Gaillard, EA
Abstract : Background: Airway inflammation in children experiencing an acute asthma exacerbation has been little studied. A previous study (1) reported high numbers of sputum inflammatory cells in children with acute asthma and a significantly lower number two weeks after the acute episode. Our principal objective was to study children after a longer follow-up period when the effects of oral steroid therapy has subsided and to compare children with asthma to a healthy control group. Methods: We collected sputum from children attending hospital with acute asthma following salbutamol bronchodilation, and, if necessary (and FEV1>50% predicted), after nebulisation with 0.9% saline. Following recovery, sputum was obtained using hypertonic-saline induction. We also studied a control group of healthy children. Sputum samples were processed within 6 hours and a differential cell-count was obtained by counting inflammatory cells on a cytospin slide (2). Results: Paired sputum samples were obtained from fifteen children (median-age 11 years) and eight controls (median-age 13.5 years). Median number of days between sputum samples for children with asthma was 82 days (range 21–313). Sputum from children with acute asthma had a higher number of inflammatory cells and a higher percentage eosinophil count than control children (p=0.025, 0.015 respectively). Sputum from children with asthma at recovery had a higher percentage eosinophil count than control children (p=0.021), but total number of inflammatory cells were not significantly different. We did not find a significant decrease in total number of cells nor percentage neutrophils or eosinophils in the sputum of children with asthma between acute episode and recovery [see table 1 ]. In children with raised sputum eosinophils (>2.5%) during acute asthma sputum eosinophilia persisted at recovery. Conclusion: Sputum inflammatory cell counts and percentage eosinophils are elevated in children with acute asthma compared to children without asthma. We found no significant difference in either total or percentage neutrophil or eosinophil count between acute asthma and recovery. In children with eosinophilia >2.5% during acute asthma this persisted at recovery. These findings have implications for our understanding of the causes of asthma exacerbations in children. Norzila MZ et al. AJRCCMed 2000:769–774 Pin I et al. Thorax 1992:25–29